The Effect of Service Quality and Delivery Timeliness on Customer Satisfaction Sicepat Express Penggilingan in 2023 - Noor Syamsu Hidayat; Riza Lestari; Aulia Rachmadini; Nurul Khaidah (Dinasti Review, 2025)
This study discusses how service quality and delivery timeliness affect customer satisfaction at SiCepat Express Penggilingan. The purpose of this study is to test and analyze the effect of service quality variables and delivery timeliness on customer satisfaction. This research uses a quantitative approach with the technique of taking respondents’ responses using purposive sampling. The total respondents’ responses were calculated using Hair's theoretical formula, resulting in 135 respondents’who are users of SiCepat Express Penggilingan services. The population in this study includes 19,529 customers of all SiCepat Express Penggilingan service users during the period January to December 2023, with an average of 1,627 customers per month. The analytical test tool used is Smart PLS 4 with the SEM (Structural Equation Modeling) analysis method. The results of this study show that the results of research with the three variables tested, namely service quality, delivery timeliness and customer satisfaction, have positive and significant results because during the hypothesis test it can be seen that the T-Statistic is 9.937 and P-Values are 0.000 < 0.05, which means Ho is rejected and Ha is accepted, so the hypothesis that reads that there is a positive influence between service quality and timeliness of delivery together on customer satisfaction can be accepted.